Weight perception analysis using pseudo-haptic feedback based on physical work evaluation - Moosavi, Mahdiyeh Sadat; Raimbaud, Pierre; Guillet, Christophe; Plouzeau, Jeremy; Merienne, Frederic (Frontiers in Virtual Reality, 2023)
Since kinesthetic cues are not present in virtual environments, users have difficulty feeling the heaviness of virtual objects. To address this issue, pseudo-haptic approaches have been proposed to illusorily induce the weight of virtual objects through the user’s visual sensory system. In this paper, we used two methods to induce the impression of virtual objects’ heaviness. One relies on the direct modification of the control-display (C/D) ratio when lifting objects, and the other depends on controlling this ratio based on a velocity restriction. We innovatively measured each approach’s efficiency by analyzing physical work as an objective metric. In addition, we used Borg CR10 to measure users’ hand fatigue during the experimental phases. Our findings are discussed in terms of individual lifting behavior in different pseudo-haptic methods. Furthermore, different virtual weight-lifting behaviors were compared to the same real-world weight-lifting behaviors. According to our results, the direct control of the C/D ratio method provides VR users with a more accurate weight perception than the velocity restriction one. Furthermore, with this first method, users’ lifting behavior was closer to the behavior when lifting real objects.